'A sort of destiny': The Multi-Jurisdictional Response to Sewage Pollution in the Great Lakes, 1900-1930 - Read, Jennifer (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1998)
ABSTRACTAt the turn of the twentieth century, water pollution was the primary vector spreading waterborne disease and a public health issue. In the Great Lakes basin, unprecedentedly high mortality from typhoid fever prompted a conference of federal and provincial public health officials in 1910. Three related initiatives resulted: the provincial government amended the Public Health Act in 1912; federal legislators attempted to develop national pollution control legislation between 1912 and 1915; the International Joint Commission investigated cross boundary pollution in 1912 and recommended a convention to control it. Of the three initiatives, only the provincial Public Health Act amendments were carried to fruition. By 1915, the almost universal adoption of chlorine treatment for municipal water supplies effectively controlled waterborne disease and there was no longer a perceived need for further action.